Differences in the influence of independent directors and commissioners on the timeliness of financial reporting with audit opinion and audit quality as moderating variables - Jurnali, Teddy; Karina, Ria; Vaustine, Khellyn; Septiany, Sheila; Wazir, Nurul Azirah Binti Mohd (Jurnal Akuntansi dan Auditing Indonesia, 2025)
This study aims to examine the differential influence of independent directors and independent commissioners on the timeliness of financial reporting, with audit opinion and audit quality as moderating variables. Using purposive sampling, data were drawn from 518 companies listed on the Indonesia Stock Exchange (IDX) between 2017 and 2021. The results indicate that independent directors have a significant negative effect on the timeliness of financial reporting. In contrast, independent commissioners do not significantly influence reporting timeliness. Furthermore, audit opinion substantially moderates the relationship between independent directors and timeliness, but not the relationship between independent commissioners and timeliness. Audit quality, however, does not moderate either of these relationship. The study results further indicate that independent directors play a more effective supervisory role in ensuring timely financial reporting compared to independent commissioners.